PALEOMORFOGENESIS BENTANG ALAM KOMPLEKS GUNUNG IJO, KULONPROGO - Rr. Amara Nugrahini; Hill Gendoet Hartono; T. Listyani R.A. (KURVATEK, 2020)
Geomorphological studies of the Mt. Ijo complex area need to be done to understand the geomorphology of the past. The purpose of the study was to identify geomorphological characteristics in order to gain an understanding of Mt. Ijo's paleomorphogenesis. The research was conducted using geomorphological observation methods in the field and assisted by rock petrographic analysis. Mt. Ijo is an old volcano that forms the West Progo Hills. The Mt. Ijo complex is composed of a predominance of igneous and volcanic rocks in the form of coherent lava and pyroclastic, in addition to sedimentary rocks in the form of limestone. The Mt. Ijo complex forms the remains of an ancient volcano. The remaining morphology is interpreted as part of the ancient volcanic body in the central and proximal facies.Keywords: Mt. Ijo, paleomorphogenesis, volcanic facies, remaining landform